A study to assess the knowledge of female medical students on polycystic ovary syndrome in NRI Institute of Medical Sciences - Malini, Marri Vasantha; Surekha, Teki (International Journal of Research in Medical Sciences, 2022)
Background: Polycystic ovary syndrome (PCOS) is a hyperandrogenic disorder with an approximate prevalence of 15% to 20%; despite being a common disease in women, an estimated 68% of the total cases remain undiagnosed. Long-term consequences of PCOS on psychological health have been underestimated and disregarded. Even though the disorder has a wide spectrum of symptoms affecting a female’s life from early teenage to later in life, it is not given as much importance as other chronic diseases like diabetes mellitus, hypertension, or a thyroid disorder. The need to address this syndrome both as a burden to the healthcare system, as well as on an individual basis right now, is of paramount importance. Previous studies have found that there was a gap in the knowledge of medical students about PCOS and its symptoms and signs, and that lifestyle preferences may predispose to PCOS. Delay in the diagnosis of PCOS may lead to metabolic and reproductive abnormalities associated with it. This study was mainly aimed at assessing the knowledge of female medical students on PCOS in NRIIMS, Sangivalasa. Methods: This was an online questionnaire based cross sectional study conducted on 550 female medical students of NRIIMS from March 2022 to September 2022 after taking approval from the institute ethics committee. The completely filled questionnaires (500) were analysed for the results. Results: In the present study though the female medical students had good knowledge regarding the causes and risk factors associated with PCOS, their knowledge about the complications of PCOS was found to be significantly less. The main source of knowledge regarding PCOS was from the treating doctor and browsing the internet being the next source. Conclusions: Effective educational intervention can significantly increase the level of knowledge on PCOS in female medical students.